Іван Климко: творча доля митця на тлі його часу - Волошин, Л. (Інститут народознавства НАН України, 2008)
The article throws some light on creative work of an artist who clearly represented aesthetic ideals spread during period of 1950s to 1990s. I.Klymko fruitfully worked in the fields of ceramics, sculpture and painting.